Remnant Cholesterol, Not LDL Cholesterol, Is Associated With Incident Cardiovascular Disease - Castañer, Olga; Pintó, Xavier; Subirana, Isaac; Amor, Antonio J.; Ros, Emilio; Hernáez, Álvaro; Martínez-González, Miguel Ángel; Corella, Dolores; Salas-Salvadó, Jordi; Estruch, Ramón; Lapetra, José; Gómez-Gracia, Enrique; et al. (Journal of the American College of Cardiology, 2020)
Genetic, observational, and clinical intervention studies indicate that circulating levels of triglycerides and cholesterol transported in triglyceride-rich lipoproteins (remnant cholesterol) can predict cardiovascular events. This study evaluated the association of triglycerides and remnant cholesterol (remnant-C) with major cardiovascular events in a cohort of older individuals at high cardiovascular risk. This study determined the baseline lipid profile and searched for major adverse cardiovascular events (MACEs) in the high-risk primary prevention PREDIMED (Prevención con Dieta Mediterránea) trial population (mean age: 67 years; body mass index: 30 kg/m2; 43% men; 48% with diabetes) after a median follow-up of 4.8 years. Unadjusted and adjusted Cox proportional hazard models were used to assess the association between lipid concentrations (either as continuous or categorical variables) and incident MACEs (N = 6,901; n cases = 263). In multivariable-adjusted analyses, triglycerides (hazard ratio [HR]: 1.04; 95% confidence interval [CI]: 1.02 to 1.06, per 10 mg/dl [0.11 mmol/l]; p < 0.001), non−high-density lipoprotein cholesterol (HDL-C) (HR: 1.05; 95% CI: 1.01 to 1.10, per 10 mg/dl [0.26 mmol/l]; p = 0.026), and remnant-C (HR: 1.21; 95% CI: 1.10 to 1.33, per 10 mg/dl [0.26 mmol/l]; p < 0.001), but not low-density lipoprotein cholesterol (LDL-C) or HDL-C, were associated with MACEs. Atherogenic dyslipidemia (triglycerides >150 mg/dl [1.69 mmol/l] and HDL-C <40 mg/dl [1.03 mmol/l] in men or <50 mg/dl [1.29 mmol/l] in women) was also associated with MACEs (HR: 1.44; 95% CI: 1.04 to 2.00; p = 0.030). Remnant-C ≥30 mg/dl (0.78 mmol/l) differentiated subjects at a higher risk of MACEs compared with those at lower concentrations, regardless of whether LDL-C levels were on target at ≤100 mg/dl (2.59 mmol/l). In overweight or obese subjects at high cardiovascular risk, levels of triglycerides and remnant-C, but not LDL-C, were associated with cardiovascular outcomes independent of other risk factors. [Display omitted]